2015
DOI: 10.1016/j.ces.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale aspects of oriented attachment

Abstract: TiO 2 nanocrystal aggregation mechanisms are quantified using molecular dynamics. In vacuum, TiO 2 nanocrystal aggregation is directed by electrostatics. In water, TiO 2 nanocrystals exhibit oriented attachment. Oriented attachment is facilitated by adsorbed water and surface hydroxyls. a b s t r a c tOriented attachment (OA), or the non-random aggregation of crystallites to form single or twinned crystals, has been observed is a variety of different systems during crystal growth. OA is believed to underlie th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…Among these, oriented attachment (OA) has received considerable attention. [6][7][8][9][10][11] OA is the aggregation of two crystallites in a way that produces a single crystal 12 or a crystal with planar defects at the attachment plane. 13 Considering all possible morphologies that could occur when two nanocrystals aggregate, we can envision many random, polycrystalline structures and a vanishingly small subset of aggregates that would exhibit OA.…”
mentioning
confidence: 99%
“…Among these, oriented attachment (OA) has received considerable attention. [6][7][8][9][10][11] OA is the aggregation of two crystallites in a way that produces a single crystal 12 or a crystal with planar defects at the attachment plane. 13 Considering all possible morphologies that could occur when two nanocrystals aggregate, we can envision many random, polycrystalline structures and a vanishingly small subset of aggregates that would exhibit OA.…”
mentioning
confidence: 99%
“…In 1998, Penn and Banfield [12,13] investigated the growth of titania nanocrystals under hydrothermal conditions through high-resolution transmission electron microscopy (HRTEM) and found that the crystal grew through oriented aggregation or oriented attachment (OA). Afterwards, adequate experimental observations confirmed the validity of the OA mechanism [14,15]. In the OA growth process, nanoparticles (building blocks) with identical crystallographic orientations directly combine together to form larger ones.…”
Section: Introductionmentioning
confidence: 65%
“…Two relevant theories have been propounded: Ostwald Ripening and "oriented attachment" (OA). The OA theory was proposed just before the dawn of the new millennium [2], after which several efforts [3][4][5][6][7][8][9][10][11] have been made to investigate this newly-born theory in the one and a half decade and a number of works has focused on the underlying physical mechanism of OA [12][13][14][15]. Aggregation and coalescence of nanoparticles is considered to be a wide spread process during crystal growth in biological and natural systems [16][17][18] as well as the synthesis of nano-scale materials [19,20].…”
Section: Introductionmentioning
confidence: 99%